Cluster Analysis using Rough Set Theory (Journal of Informatics and Mathematical Sciences, 2017)
Cluster is a group of objects of similar type and clustering is the process of finding clusters in dataset. Finding a set of clusters in a dataset is one fold of the data mining and it should be further analysis for knowledge. This paper present a method based on the concepts of Rough Set Theory to analysis the outcome of clustering process. The proposed method will able to explain the existence of clusters and why two clusters are different.
Keywords: Data mining; Clustering; Rough set theory